Agricultural Consumption Culture and Ecological Transformation:Bangladesh Perspective - Rahman, K. M. Atikur; Guozhou, Fan; Zhang, Dunfu (Asian Development Policy Review, 2017)
The paper mainly focuses the poor consumption culture and its adverse impact on environmental services. It is found the study that social regulation, values, choice and habits of Bangladesh people remain in a traditional and poor standard that cannot foster individual life as well as the socio-ecological aspects. Indiscriminate and excessive use of agro-inputs (fertilizer, insecticides, energy, and water) causes fatal risks to agro-natural resources. In addition, aquatic and livestock resources are gradually being depleted and exploited through consumption and production in unsustainable or poor sustainable way. The paper is written based on the content analysis in a qualitative approach. The documents of national and international government and non-government offices, journal articles, media report, book etc. have critically been reviewed for data collection. Mainly secondary data has been used in the study, but the empirical observation is applied herein as a primary data source also. A social movement is to be introduced within the entire stakeholder around Bangladesh. Yet, mass media, civil society, intellectuals and policy makers have to come forward to launch the movement so that the peasant community can be regulated by morals, values, principles to eradicate bad agricultural consumption and production towards sustainable development.